Aeroacoustic sources analysis of wake-ingesting propeller noise. (10th May 2023) - Yangzhou, Jianyun; Wu, Jiafeng; Ma, Zhaokai; Huang, Xun
Abstract: Abstract : High resolution aeroacoustic source analysis is a prerequisite to address the noise concerns and release the full benefits of wake-ingesting propellers. In this work, the aeroacoustic sources of a two-bladed propeller ingesting the wake of an aerofoil are investigated using large eddy simulation in conjunction with two different source identifying approaches. The first approach is the numerical beamforming that utilizes both the classical and wavelet-based beamforming techniques, which determine the phase variations of sources at the low to mid frequencies and reveal that the high-frequency sources are phase-independent. To further improve the spatial resolution of source identification, a new near-field aeroacoustic source analysis approach based on the acoustic analogy is developed in this work. In particular, the on-surface source terms emanating the far-field noise are derived based on the Ffowcs Williams and Hawkings equation for low Mach number flows and constant rotating propellers. Through the incorporation of the simulation results into the proposed source analysis approach, various types of aeroacoustic sources are identified and studied by visualizing their distributions on the propeller surfaces, correlating to flow features and examining the noise spectra and directivity. While the leading edge sources are highly correlated with the wake interaction process, the sources at the mid-chord and the trailing edge of the blade can maintain their strength across most revolving angles. Overall, the proposed analysis approaches extend the capability of computational fluid dynamics and enable the detailed study of noise generation mechanisms of wake-ingesting propeller noise.